2010
DOI: 10.1007/s10886-010-9762-x
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of a Mosquito Odorant-binding Protein Involved in the Sensitive Detection of Oviposition Attractants

Abstract: Odorant-binding proteins (OBPs) were discovered almost three decades ago, but there is still considerable debate regarding their role(s) in insect olfaction, particularly due to our inability to knockdown OBPs and demonstrate their direct phenotypic effects. By using RNA interference (RNAi), we reduced transcription of a major OBP gene, CquiOBP1, in the antennae of the Southern house mosquito, Culex quinquefasciatus. Previously, we had demonstrated that the mosquito oviposition pheromone (MOP) binds to CquiOBP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
140
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 173 publications
(149 citation statements)
references
References 9 publications
7
140
0
1
Order By: Relevance
“…CquiOBP1 binds the oviposition pheromone as well as other odorants (138,145). In a recent study, RNAi knockdown of CquiOBP1 resulted in a reduced electrophysiological response to oviposition pheromone and some, but not all, of the nonpheromonal odorants that bind to this OBP (49). This result provides an interesting opportunity to investigate the role of an OBP in the behavioral response to nonpheromonal odorants, an unresolved question in the field.…”
Section: Quinquefasciatus: a Vector Of Filariasismentioning
confidence: 88%
See 2 more Smart Citations
“…CquiOBP1 binds the oviposition pheromone as well as other odorants (138,145). In a recent study, RNAi knockdown of CquiOBP1 resulted in a reduced electrophysiological response to oviposition pheromone and some, but not all, of the nonpheromonal odorants that bind to this OBP (49). This result provides an interesting opportunity to investigate the role of an OBP in the behavioral response to nonpheromonal odorants, an unresolved question in the field.…”
Section: Quinquefasciatus: a Vector Of Filariasismentioning
confidence: 88%
“…However, OBPs seem likely to play roles in the dynamics of olfactory response and in olfactory sensitivity. Two recent studies have reported decreased electrophysiological responses to odorants when an OBP was targeted with RNAi (48,49), and variations in behavioral responses to odorants have been associated with polymorphisms in OBP genes (50,51).…”
Section: Mechanisms Of Insect Olfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…CquiOBP1 bound MOP with high affinity at high pH but showed no affinity at low pH (8). OBPs essential role for odorant reception in C. quinquefasciatus has been demonstrated by RNA interference experiments in which reduction of CquiOBP1 expression led to lower sensitivity for the detection of oviposition attractants, including MOP (12). Using CquiOBP1 as a molecular target in a reverse chemical ecology approach (10), we identified C. quinquefasciatus oviposition attractants (8), which are now commercially available for monitoring and surveillance.…”
mentioning
confidence: 99%
“…Finally, these GCaMP6s/+/+ mosquitoes and GCaMP6s/Gr3-/-and GCaMP6s/orco5-/-mutants could provide additional information and strategies for the control of disease-vector mosquitoes. Female mosquitoes may use olfactory indicators of larval habitat quality to choose oviposition sites [69] . A better understanding of chemosensory cues that elicit strong responses in larvae could help identify new attractants for use in oviposition traps, or oviposition deterrents for use in homes and outdoor water containers.…”
mentioning
confidence: 99%